The first complete mitochondrial genome assembly and comparative analysis of the fern Blechnaceae family: Blechnopsis orientalis - Huang, Yutong; Xing, Yanping; Men, Wenxiao; Xue, Hefei; Hou, Wenjuan; Huang, Yanchang; Dou, Deqiang; Kang, Tingguo; Yang, Yanyun; Xu, Liang (Frontiers in Plant Science, 2025)
IntroductionBlechnopsis orientalis (L.) C. Presl is a medicinal and edible fern species belonging to the Blechnaceae family. Currently, the complete mitochondrial genome of B. orientalis, as well as those of other Blechnaceae species, remains unreported, and studies on fern mitochondrial genome are limited.MethodsIn this study, the B. orientalis mitochondrial genome was sequenced using both Nanopore PromethION and Illumina NovaSeq 6000 platforms. Genome annotation was performed using MITOFY and MFANNOT, with structural visualization via OGDRAW. In-depth analyses were conducted, including assessments of non-synonymous/synonymous mutation ratios (Ka/Ks), codon usage bias, repeat sequence identification, RNA editing site prediction, collinearity, and the identification of homologous fragments between chloroplast and mitochondrial genomes. Finally, we employed both the maximum likelihood (ML) and Bayesian (BI) methods to analyze the phylogenetic relationships among B. orientalis and nine other fern and lycophyte species.ResultsThe mitochondrial genome of B. orientalis has a complex structure comprising 80 contigs, with a total length of 501,663 bp and a GC content of 48.53%. A total of 179 genes were identified, including 40 protein-coding genes (PCGs), 98 tRNA genes, 40 rRNA genes, and one pseudogene (rps11). Phylogenetic analysis based on PCGs from both chloroplast genome and mitochondrial genome aligned with the relationships described in the Pteridophyte Phylogeny Group I (PPG I) system. Further comparison with mitochondrial genome of ten other reported fern and lycophyte species revealed that the mitochondrial genome PCGs in these plants are highly conserved, despite significant genome rearrangements among mitochondrial genome.DiscussionThe findings of this study provide valuable insights into the evolutionary analysis of B. orientalis and contribute to understanding the characteristics and evolutionary relationships of mitochondrial genome in ferns and lycophytes.